2018
DOI: 10.1002/ange.201803180
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Functionalization of 1‐Boraphenalenes

Abstract: 1-Boraphenalenes have been synthesized by reaction of BBr 3 with 1-(aryl-ethynyl)naphthalenes,1 -ethynylnaphthalene,a nd 1-(pent-1-yn-1-yl)naphthalene and they can be selectively functionalizeda tb oron or carbon to form benchstable products.A ll of these 1-boraphenalenes have LUMOs localized on the planar C 12 Bcore that are closely comparable in character to isoelectronic phenalenyl cations.I nc ontrast to the comparable LUMOs,the aromatic stabilization of the C 5 B ring in 1-boraphenalenes is dramatically l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…For each synthesis, dehydrogenation was effected by reaction with a TEMPO radical solution at 80 °C for 24−36 h. Hydrolytic workup allowed the isolation of the desired polycyclic borinic acid products by silica gel chromatography (1−3, 5−6) or acidic aqueous extraction (4b). 1-Boraphenalene 1 (49%), 14 1,6-diborapyrene 2 (39%), 1,8-diborapyrene 3 (31%), 3,9-diboraperylene 4b (12%), 1,7-diboraanthanthrene 5 (22%), and 2,8-diboratriangulene 6 (15%) (Table 1) were characterized by multinuclear NMR spectroscopy and HRMS (see Supporting Information). Compounds 1−6 show no signs of degradation when stored as solids under ambient conditions for months.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For each synthesis, dehydrogenation was effected by reaction with a TEMPO radical solution at 80 °C for 24−36 h. Hydrolytic workup allowed the isolation of the desired polycyclic borinic acid products by silica gel chromatography (1−3, 5−6) or acidic aqueous extraction (4b). 1-Boraphenalene 1 (49%), 14 1,6-diborapyrene 2 (39%), 1,8-diborapyrene 3 (31%), 3,9-diboraperylene 4b (12%), 1,7-diboraanthanthrene 5 (22%), and 2,8-diboratriangulene 6 (15%) (Table 1) were characterized by multinuclear NMR spectroscopy and HRMS (see Supporting Information). Compounds 1−6 show no signs of degradation when stored as solids under ambient conditions for months.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We assign this as compound E (based on multinuclear NMR spectroscopy), with cis-haloboration based on an NOE experiment showing interaction between the vinylC-H and an aromatic C-H, with no other (trans-haloboration or 1,1-haloboration) isomers observed. 22,23 Previously, we have demonstrated that the addition of [BCl4] − salts can enhance the amount of the alkyne haloboration product formed in reactions where haloboration proceeds in competition with another transformation. 24 Presumably, the presence of [BCl4] − as an exogenous chloride source facilitates conversion of a vinyl cation to a vinyl chloride by chloride transfer.…”
Section: Resultsmentioning
confidence: 99%
“…In situ NMR spectroscopy revealed that one other major product is formed which contained two boron centers, one three and one four coordinate (Figures S31 and S32). We assign this as compound D , with the cis ‐haloborated alkene isomer assigned based on NOE experiments, with no other haloboration isomers observed [24, 25] …”
Section: Figurementioning
confidence: 99%